Efficacy of Dilapan S compared to foley balloon in preinduction cervical ripening—a noninferiority trialAJOG Global Reports at a Glance - Krishna Priya Leela, MS, MRCOG; Maheswari Somasundaram, MS; Zinia T. Nujum, PhD; Latha Maheshwari Subbarayan, DNB (AJOG Global Reports)
ABSTRACT: Background: The need for induction of labor is increasing in present obstetric practice. The available non-pharmacological methods for cervical ripening at term are Foley balloon and Dilapan-S. With the gaining popularity of Dilapan-S worldwide, there are very few clinical trials conducted in India to evaluate its effectiveness. Objective: To compare the efficacy of Dilapan-S and Foley balloons for pre-induction cervical ripening. Study design: This single-center randomized non-inferiority trial included primi- and multi-gravida women between 37 and 41 weeks of gestation and unfavourable cervix with a Bishop's score between 0 and 2. Using a random number table, patients were assigned to study Group 1 Dilapan-S and to control Group 2 Foley balloon. Dilapan-S or Foley balloon was inserted intracervically and assessed for dilation after 12 hours. Patients with unfavourable dilatation were further provided prostaglandins (PgE 1 and 2) for further augmentation of induction. Primary outcome measures included improvement in Bishop's score, and mode of delivery, followed by time to delivery from intervention, use of other augmentation methods, and maternal and neonatal outcomes. Results: After screening, 296 patients with Bishop score less than 2, (148 in each group) were enrolled in the study. The number of patients who had vaginal delivery was comparable between both groups (p=.72), and so were the maternal outcomes. Two cases of cord prolapse occurred with Foley balloon. Group 2 showed significant improvement in Bishop's score (p<.001), and Group 1 had a significantly higher use of augmentation with PgE1 (p-.01) and PgE2 (p<.001). The number of contractions was significantly lower in Group 1 (p<.001), and contraction intensity was higher in Group 2. There was no significant difference in cesarean delivery for failed induction of labor between the groups (p=.72). Based on the primary outcome measure, Dilapan-S was found to be non-inferior to the Foley balloon. Conclusion: Dilapan-S is non-inferior to Foley balloon in achieving pre-induction cervical ripening in term pregnancies, and therefore Dilapan-S can be suggested as an alternative in clinical practice with minimal risks.